Theoretical investigations on heteronuclear Chalcogen-Chalcogen interactions: on the nature of weak bonds between Chalcogen Centers - Bleiholder, Christian; Gleiter, Rolf (Inorganic chemistry, 2007)
To understand the intermolecular interactions between chalcogen centers (O, S, Se, Te), quantum chemical calculations on model systems were carried out. These model systems were pairs of monomers of the composition (CH3)2X1 (X1 = O, S, Se, Te) as the donors and CH3X2Z (with X2 = O, S, Se, Te and Z = Me, CN) as the acceptors. The variation of X1, X2, and Z leads to 32 pairs with 8 homonuclear cases (X1 = X2 = O, S, Se, Te) and 24 heteronuclear cases (X1 ≠ X2). The MP2/SDB-cc-pVTZ, 6-311G* level of theory was used to derive the geometrical parameters and the interaction energies of the model systems. The pairs with Z = CN (17−32) show a considerably higher interaction energy than the pairs with CH3 groups only (1−16). Natural bond orbital (NBO) analysis revealed that the interaction of the dimers 1, 2, 5, 6, 9, 10, 13, 14, 17, 21, 25, and 29 is mainly due to weak hydrogen bonding between methyl groups and chalcogen centers. These systems all contain hard chalcogen atoms as acceptors. For all other systems, the chalcogen−chalcogen interaction dominates. The one-electron picture of an interaction between the lone pair of the donor chalcogen atom and the chalcogen−carbon antibonding σ* orbital serves as a model to qualitatively rationalize trends found in many of these systems. However, it has to be applied with some amount of skepticism. A detailed analysis based on symmetry-adapted perturbation theory (SAPT) reveals that induction and dispersion forces dominate and contribute to the bonding in each case. Hydrogen-bonded compounds involve bonding electrostatic contributions. Compounds dominated by chalcogen−chalcogen interactions exhibit bonding due to electrostatic interactions only if one of the chalcogen atoms involved is sulfur or oxygen.